Analysis of Mathematical Critical Thinking Ability of Fourth Graders of Public Elementary School 001 Air Tiris - Riadoh, Riadoh; Habibi, Mhmd; Risnawati, Risnawati (Journal of Educational Sciences, 2023)
This research is motivated by the low ability of students to think critically and mathematically when solving problems. The purpose of this study was to analyze the ability to think critically mathematically in fourth grade students at public elementary school 001 Air Tiris. This research uses descriptive and qualitative research methods. The participants in this study were all children enrolled in the fourth grade at 001 Air Tiris Public Elementary School. There are 24 fourth grade students in total. The data collected is in the form of written assessments, direct interviews, and mathematical calculations. Based on the results of the research, the level of mathematical critical thinking ability of the fourth grade students at public elementary school 001 Air Tiris is included in the medium category. The average achievement of the correct answer is 50.0%. Each student has unique abilities, so teachers should give them more critical thinking practice. Teachers can develop critical thinking strategies or learning models to improve students' mathematical thinking abilities.